Smart Apps Creator: Mathematics Scientific-Based Interactive Multimedia for Improving Acceleration Program Students’ HOTS - Qur’ani, Fauziyah Nafisatul; Wulan, Eka Resti; Syamsudin, Ahmad (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
It was found that the use of learning media in the form of modules and learning videos is not interactive so they make students feel bored and less active when the learning process. It causes students to have difficulty solving HOTS-type questions. Thus, this study aims to develop scientific-based interactive mathematics multimedia to increase the HOTS of accelerated students on similarity and congruence materials with the help of the Smart Apps Creator. This study uses the R&D method with the ADDIE model. The data analysis technique in this research is descriptive and uses paired samples t-test. The instruments are a questionnaire for material and media expert validation, a questionnaire for teacher and student responses, a pre-test, and a post-test. The results of the validation of the material expert obtained the